2019
DOI: 10.4274/jpr.galenos.2019.93276
|View full text |Cite
|
Sign up to set email alerts
|

Six Clinical Predictors for Intractable Childhood Epilepsy

Abstract: This study aimed to determine the significance of six clinical predictors associated with medically intractable childhood epilepsy. Materials and Methods: A retrospective cohort study was conducted. A total of 241 children with diagnosed epilepsy were recruited and divided into two groups: 61 patients with intractable epilepsy, and the other 180 patients who responded well to antiepileptic drugs. We investigated seizure semiology, etiology of epileptic encephalopathy, EEG abnormalities and defined the odds rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 18 publications
(23 reference statements)
1
2
0
Order By: Relevance
“…In the present study, a positive family history of seizures was not identified as a predictor of drug resistance. This is consistent with Ayca and colleagues [ 11 ], who showed that a positive family history of seizures did not seem to be a risk factor for drug-resistant epilepsy. Other studies found no significant correlation between a family history of seizures and drug-resistant epilepsy [ 10 , 12 , 13 ].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In the present study, a positive family history of seizures was not identified as a predictor of drug resistance. This is consistent with Ayca and colleagues [ 11 ], who showed that a positive family history of seizures did not seem to be a risk factor for drug-resistant epilepsy. Other studies found no significant correlation between a family history of seizures and drug-resistant epilepsy [ 10 , 12 , 13 ].…”
Section: Discussionsupporting
confidence: 92%
“…The association between developmental delay and negative outcomes may result from minor but widespread brain anatomical abnormalities [ 10 ]. Hypoxic or asphyxic events, mainly in the perinatal period, promote epileptogenesis and are important in developing drug resistance [ 11 ]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation